2(3(x-2))=8x-24

Simple and best practice solution for 2(3(x-2))=8x-24 equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for 2(3(x-2))=8x-24 equation:


Simplifying
2(3(x + -2)) = 8x + -24

Reorder the terms:
2(3(-2 + x)) = 8x + -24
2((-2 * 3 + x * 3)) = 8x + -24
2((-6 + 3x)) = 8x + -24
(-6 * 2 + 3x * 2) = 8x + -24
(-12 + 6x) = 8x + -24

Reorder the terms:
-12 + 6x = -24 + 8x

Solving
-12 + 6x = -24 + 8x

Solving for variable 'x'.

Move all terms containing x to the left, all other terms to the right.

Add '-8x' to each side of the equation.
-12 + 6x + -8x = -24 + 8x + -8x

Combine like terms: 6x + -8x = -2x
-12 + -2x = -24 + 8x + -8x

Combine like terms: 8x + -8x = 0
-12 + -2x = -24 + 0
-12 + -2x = -24

Add '12' to each side of the equation.
-12 + 12 + -2x = -24 + 12

Combine like terms: -12 + 12 = 0
0 + -2x = -24 + 12
-2x = -24 + 12

Combine like terms: -24 + 12 = -12
-2x = -12

Divide each side by '-2'.
x = 6

Simplifying
x = 6

See similar equations:

| 2x-(-1)=6 | | 2pir=10 | | -5j-13=13 | | 5y(2x+7)+4(2x+7)=0 | | -7x+19+9x+19=4 | | (4x+y)(x-2y)= | | 2x(0)-3y=6 | | 8-(2a+7)=a+40 | | X^3-x^2+x=1 | | 7.26x+7.26=14.52 | | X+4=-5x-7 | | 6x+8=8-x | | 7(Y-1)=-42 | | 3(4-a)=2(a+6) | | -13(n+20)=(-11n+38) | | 0=9x^2-2kx+3k | | 9-x*1/2=13 | | 24=2/3V | | 5/12/360 | | -2x-3y=-30 | | 2.25+3.50x=44.25 | | 360/6x | | 2(10x-5)=4(5x+2) | | 14p+20q+p-7q-3p= | | 44.25=2.25+3.50x | | 6/7=3V | | 2-3(y-5)=3+(y+1) | | 4z+6= | | 2t-4s-2t+4s= | | (4b+7)-(6b-3)= | | 12=n-10 | | -x-5y=-54 |

Equations solver categories